(untitled) (GEOmedia, 2025)
The IV International Conference of Aerial Archaeology (Rome, 2025) represented a critical crossroads for the evolution of the discipline: from historical archives to machine learning, from theoretical reflections on landscape to scientific dissemination, the sessions outlined a multidimensional archaeological practice, oriented towards the dynamic and project-based reconstruction of the past.